Clash of Civilization in the News Reality Construction of the Anti-Ahok Rally in Kompas and Republika Newspapers - Syafruddin Ritonga; Hasrat Efendi Samosir; Muhammad Luthi; Junaidi Junaidi; Eko Nugroho (Ikatan Sarjana Komunikasi Indonesia, 2020)
The rally of around two million Muslims in Jakarta in November 2016 protesting against alleged religious defamation committed by Jakarta Governor Basuki Tjahaja Purnama made the headlines in Indonesian mainstream newspapers; Kompas and Republika. However, both newspapers came out with different perspectives in accordance with their ideological background. Therefore, these differences lead to the question of whether they would trigger a clash of civilization as pointed by S. Huntington stating that the vast post-cold war conflicts would be represented by Western Civilization, China Civilization, and Islam Civilization. This study formulates the problems including: (1) How is the clash of civilization built through the symptoms constructed in Kompas and Republika newspapers? and; (2) How do the intertextual aspects build the clash of civilization semiotically through the texts of the news in Kompas and Republika related to the November 4, 2016 rally? The paradigm used is the critical paradigm with qualitative approach, while the data are analyzed by using Kristeva Semiotic Method. The results of the research include; the mass media has been a field of the symbolic war among civilizations, meaning that the clash of civilizations on media is manifested through the symbolic conflict upheaval operated semiotically by Kompas and Republika. The news of November 4, 2016 rally in both newspapers serves as a battlefield of meanings as well as the field of a clash of civilizations.